ANALISIS KADAR AIR SERASAH KELAKAI (Stenochlaena palustris Burm. Bedd) TERHADAP PELUANG TERJADINYA KEBAKARAN DI KAWASAN EKOWISATA BEKANTAN PT. ANTANG GUNUNG MERATUS KALIMANTAN SELATAN - Mei Wulansari; Normela Rachmawati; Susilawati Susilawati (Jurnal Sylva Scienteae, 2020)
Bekantan ecotourism area is a peat area that had caught fire in 2015 resulting in the loss of existing vegetation. Naturally, areas of burned peat have the ability to repair themselves by natural (secondary) succession. This succession is usually marked by the presence of pioneer plant types which will eventually form vegetation of shrubs, one of which is kelakai (Stenochlaena palustris Burm. Bedd) which dominates in the bekantan ecotourism area. It is possible to become one of the forest fuels if the area burns again. The aim of this study is to calculate the level of water litter (Stenochlaena palustris Burm. Bedd) and analyze the effect of water content of litter (Stenochlaena palustris Burm. Bedd) on the chance of a fire in Bekantan Ecotourism Area of PT. Antang Gunung Meratus, Kalimantan Selatan. The study was conducted in Bekantan Ecotourism Area PT. Antang Gunung Meratus, Kalimantan Selatan, for 3 months, from June to August 2019. The data obtained were calculated on the water content and determined the level of fire hazard. The results of this study the water content of litter under the shade of 11.6%. So that the water content under the shade is at a rate <20%. In accordance with the statement of the Ministry of Forestry and Forestry (1999) for peatlands, the water content in the observation plots is categorized as prone to fire.Keywords: Fire; Kelakai; Water content